Public perceptions of pharmacy services: Perceived importance and face-to-face preference across service stages in the era of digital health - Dong-Wook Yang; Youran Noh; Kyung-Bok Son (Digital Health)
Background In the era of digital health, pharmacy services are rapidly evolving, yet remote service delivery remains legally restricted in South Korea. This study addresses the public perception of pharmacy services, with a particular focus on perceived importance and preferences for face-to-face interactions across the predispensing, dispensing, and postdispensing stages, especially in relation to patient–pharmacist communication. Methods A web-based survey was conducted with 1000 South Korean adults to quantify perceived service importance and delivery mode preferences across each service stage. Respondents were categorized into Assertive, Passive, and None groups based on their perceived style of communication with pharmacists. Results Participants were classified into Assertive (17.2%), Passive (54.0%), and None (28.8%) communication groups. Pharmacy services were analyzed by stage—predispensing, dispensing, and postdispensing—and perceptions of service importance, actual provision, and preferences for face-to-face delivery varied accordingly. The dispensing stage was consistently rated highest across all measures, and communication style was positively associated with each measure. Prior telemedicine experience was linked to greater openness to remote services, whereas digital health literacy showed no significant association. Conclusion Face-to-face interactions remain essential for pharmacy service delivery, particularly during the dispensing and counseling stages. Preferences for delivery methods vary by communication style, underscoring the importance of fostering effective patient–pharmacist communication. To enhance trust, satisfaction, and adherence, future models should integrate digital health technologies with meaningful in-person engagement.